(untitled) (Research, Society and Development, 2022)
The objective was to identify the sociodemographic and clinical profile of users assisted by a Family Health Strategy in Crato-CE. This is a documentary, cross-sectional, descriptive study with a quantitative approach, based on 910 household and territorial registration forms and 3,015 individual e-SUS records of patients assisted by an FHS in the urban area of the city of Crato-CE, in the period from April 2019 to February 2020. There was a predominance of females, average age of 34 years, monthly income of one minimum wage, home ownership, low schooling and people who do not work as the situation of sovereignty in the labor market job. On the other hand, the most prominent clinical characteristics were hypertension, respiratory diseases, diabetes and mental health problems. Finally, it is necessary to appropriate and understand the profiles traced in the study by the health professionals of the participating FHS in order to cross the relationship of sociodemographic variables with the clinics, to trace the profile of the user affected by certain pathologies, help in monitoring individuals more susceptible to certain diseases and contributing to faster and more effective health actions for the public in a situation of vulnerability to illness.